Pengembangan Media Video Animasi Berbasis AI “KIDANA” pada Pembelajaran PAI Kelas IV SD - Nina Kania Dwi; Ani Nur Aeni; Mely Siti Rahmawati (Lembaga Yasin AlSys, 2026)
Education plays a pivotal role in shaping individuals holistically amid globalization, which is marked by advances in information and communication technology, thereby necessitating innovative, interactive learning media aligned with learners’ characteristics. This study aims to explore the potential development of an instructional medium in the form of an artificial intelligence (AI)-based animated video named “KIDANA” to support Islamic Religious Education (PAI) learning. The research employed a Design and Development (D&D) approach encompassing the stages of design, validation, and trial with Grade IV students at SDN Cimeuhmal. The research instruments consisted of validation questionnaires for media experts and material experts, as well as student response questionnaires. The validation results show that “KIDANA” obtained an average score of 92% from media experts and 90% from material experts, both categorized as “highly feasible.” A limited trial involving 17 students yielded positive responses with a percentage of 90%, reflecting high interest and improved student understanding of Islamic Religious Education content. These findings indicate that AI-based animated video media is not only suitable for use but also effective in creating interactive and engaging learning, while offering a more personal and adaptive learning approach aligned with students’ needs in the digital era. This study contributes to the development of innovative teaching methods and demonstrates the potential of leveraging AI technology to enhance the effectiveness and efficiency of educational processes. Keywords: Artificial Intelligence; Animated Video; Design and Development; Islamic Religious Education; Innovative Learning Media